2018
DOI: 10.21608/jpp.2018.36345
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nano Material Lithovit on Growth, Flowering and Chemical Composition of Echinacea purpurea (L.).

Abstract: Two field experiments at (2016-2017) seasons were conducted to study the effect of lithovit at concentrations of 1 and 2 g/l for once, twice and thrice times application individually at 30 days interval to improve vegetative growth, flowering and chemical contents of Echinacea purpurea (L.) The obtained results showed that spraying Echinacea purpurea (L.) plants with lithovit at 2g/l for three times application in the form of foliar sprays at 30 days interval led to improve plant growth and yield characters ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…In cucumber, Lithovit increased N, P, K, Ca, Zn, and B in the foliage [113]. In Echinacea purpurea, Lithovit increased N, P, and K content [115], while in soybean foliage, the content of N, P, K, Ca, Mg, and Fe increased [114]. The results of these studies demonstrate how the effect on nutrients of nano-CaCO 3 application varies for different crops; further studies would be needed to investigate the effect of nano-CaCO 3 biostimulant application on plant nutrients in cabbage.…”
Section: Mineral Biostimulants (Nano-caco 3 )mentioning
confidence: 93%
See 1 more Smart Citation
“…In cucumber, Lithovit increased N, P, K, Ca, Zn, and B in the foliage [113]. In Echinacea purpurea, Lithovit increased N, P, and K content [115], while in soybean foliage, the content of N, P, K, Ca, Mg, and Fe increased [114]. The results of these studies demonstrate how the effect on nutrients of nano-CaCO 3 application varies for different crops; further studies would be needed to investigate the effect of nano-CaCO 3 biostimulant application on plant nutrients in cabbage.…”
Section: Mineral Biostimulants (Nano-caco 3 )mentioning
confidence: 93%
“…Due to their similar composition, the results from the foliar application of Lithovit might be relevant when investigating the effects of foliar nano-CaCO 3 biostimulant applications. When applied foliarly to cucumber, broccoli, Echinacea purpurea, soybean, and potato, the beneficial effects of Lithovit were numerous: increased vegetative growth characteristics (plant height, number of leaves, leaf area, and dry matter), increased chemical constituents (chlorophyll, carotenoids, total carbohydrates, nutrients), increased productivity and total yield, and increased total sugars and phenol compounds [106,[112][113][114][115].…”
Section: Mineral Biostimulants (Nano-caco 3 )mentioning
confidence: 99%
“…Many recent researches have shown that lithovit applied by foliar spraying increases significantly the growth and yield of medicinal plants (Abou-shlell et al, 2017;Hamed, 2018;Abd El-baset, 2018;Helaly and Hegazy, 2019). Hamed (2018) found that foliar spray with lithovit to Origanum syriacum plants significantly increased growth, herb and oil yield characters compared to untreated plants.…”
Section: Introductionmentioning
confidence: 99%